2020
DOI: 10.11591/edulearn.v14i4.16414
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ classroom instruction reinforcement strategies in english language class

Abstract: In the context of this study, reinforcement is an act of teachers to strengthen students' positive behaviour in learning English in the classroom. This qualitative case study was a classroom discourse which employed necessary quantification. The aim was to investigate the use of classroom instruction reinforcement strategies by two English language teachers and their perceptions at a state secondary school in Semarang in the academic year of 2019. The two English teachers were observed in five different lesson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…The finding of Aida & Antoni (2017) showing that pre-service teachers used of praise word and statement in the class. Fitrianti et al (2020) state that teachers in the present study employ three type of reinforcement. The reinforcement are verbal reinforcement, token reward, and tangible reward.…”
Section: The Application Of Reinforcement Skill Componentsmentioning
confidence: 94%
“…The finding of Aida & Antoni (2017) showing that pre-service teachers used of praise word and statement in the class. Fitrianti et al (2020) state that teachers in the present study employ three type of reinforcement. The reinforcement are verbal reinforcement, token reward, and tangible reward.…”
Section: The Application Of Reinforcement Skill Componentsmentioning
confidence: 94%
“…The EFL teacher believed by complimenting them in both languages (or code-switching them), they could be encouraged and motivated to participate more. True to this, a study conducted by Fitriati et al (2020) in an Indonesian EFL class has found that employing the reinforcement strategy strengthens positive behaviours and increases students-teachers interactions.…”
Section: Instructional Functions In the Teacher's Online Classroom Co...mentioning
confidence: 95%
“…Data yang sudah terlumpul kemudian dianalisis data induktif kualitatif model (Matthew B & Huberman, 1994) meliputi reduksi data, penyajian data dan penarikan kesimpulan. Pemberian penguatan dalam proses pembelajaran memberi kontribusi dalam meningkatkan keaktifan siswa (purnamasari, Marhaeni, & Artini, 2018), oleh karena itu guru dalam mengawali pembelajaran perlu melakukan penguatan dan juga motivasi kepada siswa sebagai pemicu awal agar siswa aktif dalam pembelajaran yang akan dilakukan (Fitriati, Fatmala, & Anjaniputra, 2020). Penelitian oleh Asmuni (2020) menguatkan bahwa beberapa solusi yang dapat dilakukan dalam pembelajaran daring adalah bagaimana guru mampu menyipakan materi yang menarik.…”
Section: Metodeunclassified